A Dukungan Polri dalam Kegiatan Ekstrakurikuler Pramuka terhadap Peningkatan Soft Skill Siswa-Siswi SMPN 1 KUDU: Dukungan Polri dalam Kegiatan Ekstrakurikuler Pramuka terhadap Peningkatan Soft Skill Siswa-Siswi SMPN 1 KUDU - Himawan, Agung (Jurnal Litbang Polri, 2025)
ABSTRACT Since 2022, the independent learning curriculum has been launched, Indonesian children are educated with a humanizing learning concept approach in order to awaken students' interests, talents, potential and creativity towards a golden Indonesia 2045. This is certainly not easy for teachers to do, so that through the Scouting extracurricular it is hoped that it can help shape students' character. The realization of the ideals of a golden Indonesia 2045 is a shared task and responsibility, namely the government, schools, parents and also stakeholders. The Indonesian National Police (Polri), which is a state institution that is always in touch with the community, is also present in supporting the realization of the ideals of a golden Indonesia 2045. The purpose of this study is to describe and illustrate in detail the support of the Police and the impact of Scouting extracurricular activities on improving the soft skills of students at SMPN I Kudu Jombang. This study uses a descriptive qualitative method. The results of the study showed (1) Polri provided support and was present at Scout activities at SMPN I Kudu, such as in marching exercises, rope exercises, code exercises, camping and hiking, (2) The impact of Scout activities at SMPN I Kudu on improving students' soft skills, including self-confidence, communication, teamwork, discipline, responsibility, having ideals and growing leadership. Keywords: Polri support, Scout extracurricular activities, soft skills